Seasonal influence on wing phenotypic plasticity in Mansonia indiana (Diptera: Culicidae) along the Thailand-Myanmar border - TANAWAT CHAIPHONGPACHARA; SUCHADA SUMRUAYPHOL; SEDTHAPONG LAOJUN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chaiphongpachara T, Sumruayphol S, Laojun S. 2025. Seasonal influence on wing phenotypic plasticity in Mansonia indiana (Diptera: Culicidae) along the Thailand-Myanmar border. Biodiversitas 26: 2253-2260. Mansonia indiana (Diptera: Culicidae) is a vector of the nematode Brugia malayi that causes lymphatic filariasis in Southeast Asia. Thus, this study aimed to investigate the seasonal wing phenotypic plasticity of M. indiana collected along the Thailand-Myanmar border, employing landmark-based geometric morphometrics. Sampling was conducted from September 2021 to August 2022, encompassing three distinct seasons: the cool season (November-February), the hot season (March-May), and the rainy season (June-October). The Centroid Size (CS) ranged from 2.89 to 4.14 mm, with the cool season population recording the highest average CS at 3.68 mm and the rainy season population the lowest at 3.44 mm. Significant differences (p<0.05) in CS were observed between the cool and rainy season populations, as well as between the cool and hot season populations. Shape analysis revealed significant differences (p<0.05) across population pairs, underscoring the pronounced impact of seasonal influences on wing shape. Wireframe graphs indicated that landmarks 1, 12, and 18 exhibited high variation, suggesting a seasonal influence on wing structures. The unweighted Pair Group Method with Arithmetic Mean tree analysis, based on Mahalanobis distances, indicated that the cool-season population exhibited the most distinct shape. These findings indicate that variations in wing morphology may represent adaptive responses by mosquitoes to the varied environmental pressures of each season. Additionally, wing morphology influences flight efficiency, which is essential for effective host attacks and plays a crucial role in the transmission of filariasis to humans.